Hyperphosphatemic Tumoral Calcinosis: Pathogenesis, Clinical Presentation, and Challenges in Management - Boyce, Alison M.; Lee, Alisa E.; Roszko, Kelly L.; Gafni, Rachel I. (Frontiers in Endocrinology, 2020)
Hyperphosphatemic familial tumoral calcinosis (HFTC) is a rare and disabling disorder of fibroblast growth factor 23 (FGF23) deficiency or resistance. The disorder is manifest by hyperphosphatemia, inappropriately increased tubular reabsorption of phosphate and 1,25-dihydroxy-Vtamin D, and ectopic calcifications. HFTC has been associated with autosomal recessive pathogenic variants in: 1) the gene encoding FGF23; 2) GALNT3, which encodes a protein responsible for FGF23 glycosylation; and 3) the gene encoding KLOTHO, a critical co-receptor for FGF23 signaling. An acquired autoimmune form of hyperphosphatemic tumoral calcinosis has also been reported. Periarticular tumoral calcinosis is the primary cause of disability in HFTC, leading to pain, reduced range-of-motion, and impaired physical function. Inflammatory disease is also prominent, including diaphysitis with cortical hyperostosis. Multiple treatment strategies have attempted to manage blood phosphate, reduce pain and inflammation, and address calcifications and their complications. Unfortunately, efficacy data are limited to case reports and small cohorts, and no clearly effective therapies have been identified. The purpose of this review is to provide a background on pathogenesis and clinical presentation in HFTC, discuss current approaches to clinical management, and outline critical areas of need for future research.